Empathy in autism spectrum disorder: Predictions from child/adolescent temperament, parenting styles, and parenting stress - Ross, Toni Carmen Faith (Department of Psychology, 2020)
Individuals with autism spectrum disorder (ASD) exhibit definitional impairments in social relatedness; a phenomenon that can be explained, in part, by their deficits in empathy. Despite the extent of these deficits, relatively little is known about which factors promote or impede empathic functioning within this group. To date, studies of neurotypical children and adolescents suggest the explanatory power of temperament, parenting style, and parenting stress; associations which have yet to be adequately explored with ASD. Thus, the overarching aim of this investigation was to test whether the aforementioned intra- and interindividual features would predict empathy amongst children and adolescents with ASD. To account for some of the heterogeneity in ASD, two groups of parent-child dyads were recruited: one comprising male children and adolescents with intact receptive and expressive language (n = 40, M = 7.68 years); the other, males with little to no language use in either domain (n = 40, M = 9.09 years). A third group of parent-child pairs comprising male neurotypical children and adolescents with age-appropriate language functioning was included as a comparison sample (n = 40, M = 9.53 years). Parents completed wellestablished questionnaires pertaining to child/adolescent temperament and empathy, as well as parenting style and parenting stress, primarily via telephonic interviews. Results showed that temperamental regulation and negative affectivity were linked to empathy within the neurotypical group in positive and inverse directions, respectively. Only regulatory processes were positively associated with empathy within the non-verbal ASD group, whilst only negative affectivity was inversely associated to empathy within the verbal ASD group. Further, warm, responsive, autonomy-promoting parenting was positively associated with empathy within the neurotypical group, whilst punitive and lax parenting were inversely associated with empathy. Positive forms of parenting were also found to predict empathy within both ASD groups – though somewhat less so within the verbal ASD group. Perhaps a consequence of the severity of their empathic deficits, lax and permissive parenting techniques were not tied to empathy within the ASD groups. Finally, parenting stress was inversely linked to empathy within the non-verbal ASD and neurotypical groups only. Results highlight that findings obtained within neurotypical samples cannot always be extrapolated to ASD. Results further underscore the need for ASD interventions to adopt a family systems perspective, teaching parents how to perceive and respond to their children in adaptive ways.